2011
DOI: 10.2485/jhtb.20.147
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted Bone Marrow derived Cells Differentiated toTooth, Bone and Connective Tissues in Mice

Abstract: Teeth are important structures for masticatory and phonetic purposes. Loss of teeth decreases these functions leading to impaired quality of life. Missing teeth replaced by tooth regeneration may be possible with emerging advances in stem cell biology and tissue engineering. Recent investigations have demonstrated that bone marrow derived cells (BMDC) can differentiate into cells other than blood cells. In the present study, the ability of BMDC to differentiate into tooth forming tissues was investigated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
(26 reference statements)
2
15
0
Order By: Relevance
“…This coincides with previous findings, which showed that BMDCs have the possibility of migrating into many organs presenting microchimerism after transplantation in irradiated mice 7,9,12,[19][20][21] . Salivary gland tissues are composed of various types of cells, which originate from mesenchymal stem cells (MSCs) 22) .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This coincides with previous findings, which showed that BMDCs have the possibility of migrating into many organs presenting microchimerism after transplantation in irradiated mice 7,9,12,[19][20][21] . Salivary gland tissues are composed of various types of cells, which originate from mesenchymal stem cells (MSCs) 22) .…”
Section: Discussionsupporting
confidence: 80%
“…confirmed many times in our previous studies 9,19) . One month after BMT, HE staining of recipient mice revealed there was almost no apparent damage in the salivary gland parenchyma (Fig.…”
Section: Jhard Tissue Biology Vol 22(4):433-438 2013supporting
confidence: 78%
“…Kaneko et al 13) also showed that the periodontal ligament fibroblasts were derived from the bone marrow. On the other hand Tsujigiwa et al 14) showed that bone marrow mesenchymal cells could also differentiate into odontogenic cells. Hence, further analysis to clarify the nature of cells making up the periodontal membrane polyp is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The study also revealed that the mesenchymal stem cells differentiated into a variety of cell types in their local destination [12][13][14][15] . Therefore, the present experiment system together with GFP bone marrow transplant mice established by Tsujigiwa et al 10) would contribute greatly to the understanding of the mechanism in the formation of chronic apical periodontitis.…”
Section: Discussionmentioning
confidence: 98%